2019
DOI: 10.1002/cphc.201900141
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Photocatalytic Properties of Pt/CeOx/TiO2: Structural Effects on Electronic and Optical Properties

Abstract: Ceria‐titania interfaces play a crucial role in different chemical processes but are especially promising for the photocatalytic splitting of water using light in the visible wavelength region when Pt is added to the system. However, the complexity of this hierarchical structure hampers the study of the origin of its outstanding properties. In this article, the structural, electronic and optoelectronic properties of CeO2/TiO2 systems containing 1D, 2D, and 3D particles of ceria are analyzed by means of density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Titanium di-oxide has been considered to be one of the best compounds for super-capacitor electrodes. The reasons that make it excellent option are best chemical stability, low fabrication cost, non-toxic in nature, huge availability and large surface area, which gives a capacity value of 235.6 Fg −1 at current density of 0.5 Ag −1 [91,92]. This capacitance value, nevertheless, should only be achieved at an ideal size below 10 nm with ultrathin sheets or Nano-scaled particles [93,94].…”
Section: Transition Metal Oxides-graphene Compositesmentioning
confidence: 99%
“…Titanium di-oxide has been considered to be one of the best compounds for super-capacitor electrodes. The reasons that make it excellent option are best chemical stability, low fabrication cost, non-toxic in nature, huge availability and large surface area, which gives a capacity value of 235.6 Fg −1 at current density of 0.5 Ag −1 [91,92]. This capacitance value, nevertheless, should only be achieved at an ideal size below 10 nm with ultrathin sheets or Nano-scaled particles [93,94].…”
Section: Transition Metal Oxides-graphene Compositesmentioning
confidence: 99%
“…Namely, the interaction between the Pt-vacancy cluster and H 2 O is a key to consider the homogeneous electrical double layer on the active site on the cathode. However, the previously published work 76 only calculated the formation energies and adsorption energies of the single Pt atom and Pt-vacancy clusters. The adsorption energy of H 2 O on active sites on the cathode was unconsidered.…”
Section: Results and Discussion Sectionmentioning
confidence: 99%
“…However, it is well-known that the (111) surface of CeO 2 is the most thermodynamically stable surface, and this conclusion had been confirmed by dynamic force microscopy, scanning tunneling microscopy, and computer simulations. 76−82 In addition, the Pt adsorption energy on the CeO 2 (110) surface (−2.36 to −2.73 eV) in the previously published work 75 was much lower than that on the CeO 2 (111) surface (−5.0 to −6.7 eV). It means that the use of the CeO 2 (111) surface in the modeling work is essential for reasonable design of the active interface between Pt and CeO 2 .The authors concluded that the defect clusters were formed in the Pt-nanocoated layer on the CeO x NW based on microanalysis data by following defect cluster formation reactions and the combination of those clusters.…”
Section: Modeling For a Conclusion About The Role Of A Pt-nanocoated ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Insights into the impact of Pt on CeO 2 can be gleaned from Plata's research. [67] The study conducts an in-depth investigation into the electronic and photoelectronic properties of layered nanostructures in TiO 2 /CeO 2 and Pt/CeO 2 -doped TiO 2 systems. Computational analysis demonstrates that the formation of O v reduces the adsorption energy of Pt, regardless of the vacancy's location.…”
Section: Ptà Ceomentioning
confidence: 99%